Pricing strategies for a taxi-hailing platform - Wang, Xiaolei; He, Fang; Yang, Hai; Oliver Gao, H. (Transportation research. Part E, Logistics and transportation review, 2016)
•Aggregate taxi market equilibrium under hybrid modes is modeled.•Existence and stability of taxi market equilibrium are examined.•Impacts of platform’s pricing strategies on taxi market performance are revealed.•Properties of desirable price perturbations are characterized. Taxi hailing apps that facilitate taxi-customer matching quickly become popular in recent years. By combining the theories of two-sided market and taxi market, this paper models the taxi market in the presence of a single taxi hailing app through an aggregate and static approach. Based on the equilibrium model, the existence and stability of equilibria are examined, and a partial-derivative-based sensitivity analysis is conducted to quantitatively evaluate the impacts of the platform’s pricing strategies to the taxi market performance. The features of desirable price perturbations that improve social welfare and/or the platform’s profitability are also characterized.